2021
DOI: 10.3390/foods10112522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Smoking and Natural Antioxidants on Quality Traits, Safety and Shelf Life of Farmed Meagre (Argyrosomus regius) Fillets, as a Strategy to Diversify Aquaculture Products

Abstract: Aquaculture has been playing a leading role over the years to satisfy the global growing demand for seafood. Moreover, innovative techniques are necessary to increase the competitiveness, sustainability and profitability of the seafood production chain, exploiting new species from the aquaculture, such as meagre (Argyrosomus regius), to develop value-added products and diversify their production. In the present work, the effectiveness of cold smoking combined with antioxidants (SA) compared to cold smoking alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…This decrease also proceeded to different percentages from day 1 to day 90 of storage in both CSF and HSF covered with or without 0.5 and 1% of the extract. Similar results of the significant reduction in PUFAs at the end of smoking (90 days) due to a decrease in PUFAs of the n-3 series (Tot n-3) and a simultaneous increase in MU-FAs have been found in Argyrosomus regius fillets cold-smoked in combination with 1% Halocnemum strobilaceum antioxidant for 35 days of storage at 4 °C (Messina et al, 2021). In comparison with the previous work on S. lucioperca, the current increase in total SAFs is consistent with that also found in CSF and HSF by Bouriga et al (2022).…”
Section: Total Fatty Acid (Fa) Composition In Fresh Cold- and Hot-smo...supporting
confidence: 75%
“…This decrease also proceeded to different percentages from day 1 to day 90 of storage in both CSF and HSF covered with or without 0.5 and 1% of the extract. Similar results of the significant reduction in PUFAs at the end of smoking (90 days) due to a decrease in PUFAs of the n-3 series (Tot n-3) and a simultaneous increase in MU-FAs have been found in Argyrosomus regius fillets cold-smoked in combination with 1% Halocnemum strobilaceum antioxidant for 35 days of storage at 4 °C (Messina et al, 2021). In comparison with the previous work on S. lucioperca, the current increase in total SAFs is consistent with that also found in CSF and HSF by Bouriga et al (2022).…”
Section: Total Fatty Acid (Fa) Composition In Fresh Cold- and Hot-smo...supporting
confidence: 75%
“…Similar results were obtained by Chaula et al ( 2019 ) who demonstrated that the aqueous extracts of Syzygium aromaticum and Kappaphycus alvarezii protected fish ( Rastrineobola argentea ) lipids against oxidation during sun drying. Messina et al ( 2019 , 2021 ) also showed that cold smoking combined with antioxidants had a positive effect on lipid peroxidation of meager ( Argyrosomus regius ) fillets, lower values of malondialdehyde, and protected omega‐3 in fish during the process. Moreover, as in the case of Sander lucioperca filets, a fatty fish species, the lipid oxidation results showed that the combined application of Dunaliella salina as natural antioxidant and smoking significantly reduced the oxidation in Sander lucioperca in comparison with the batch that was only smoked (Bouriga et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…A great number of herbs and spices have the potential to delay lipid oxidation during food storage, usually mediated by the intrinsic antioxidant activities of their constituents. Lately, the use of natural antioxidants has increased in the food industry, and many studies have been reported on the subject (Delfino et al, 2021;Demir et al, 2014;Mahdavi and Ariaii, 2021;Messina et al, 2021;Özdemir et al, 2022;Rathod et al, 2021;Saati et al, 2022;Sengun et al, 2019;Trabelsi et al, 2021).…”
Section: Physical and Chemical Analysismentioning
confidence: 99%